-3y-23=5y+17

Simple and best practice solution for -3y-23=5y+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3y-23=5y+17 equation:


Simplifying
-3y + -23 = 5y + 17

Reorder the terms:
-23 + -3y = 5y + 17

Reorder the terms:
-23 + -3y = 17 + 5y

Solving
-23 + -3y = 17 + 5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5y' to each side of the equation.
-23 + -3y + -5y = 17 + 5y + -5y

Combine like terms: -3y + -5y = -8y
-23 + -8y = 17 + 5y + -5y

Combine like terms: 5y + -5y = 0
-23 + -8y = 17 + 0
-23 + -8y = 17

Add '23' to each side of the equation.
-23 + 23 + -8y = 17 + 23

Combine like terms: -23 + 23 = 0
0 + -8y = 17 + 23
-8y = 17 + 23

Combine like terms: 17 + 23 = 40
-8y = 40

Divide each side by '-8'.
y = -5

Simplifying
y = -5

See similar equations:

| 7x+3=-3+5x+16 | | 24-y=(-9) | | b^2+15b+54=0 | | 4(x+2)-8(3x+6)=9(4x+8) | | 8+-2(a+-1)=5+a | | 4*(x+2)-8*(3x+6)=9*(4x+8) | | 8-2(a-1)=5+9 | | 4x+16+40=160 | | 8-2(a-1)=7+9 | | 3+7n=31 | | 4p-10=-2p+14 | | 15-3n=9 | | 9p-7=4p+23 | | 11-2(9-1)=4+9 | | -5(x-2)=15 | | 5x+40=8x | | 5p+5=2p+20 | | -4(x-6)+7=31 | | 5*x+7=3*x+19 | | u^2-7u+6=0 | | 6*x-24=2*x | | 9k^3+6k^2-5k+6=0 | | -6y+2=-4(2y+4) | | 6.5y=-63.7 | | -3+x-5=-13+9-8 | | 20X+10Y=-10X+15X-5Y | | 2x-5*2=25 | | 0=x^2+2x+6 | | x^5=0.4 | | 3x+40=50+2x | | 8-7x=37-14x | | 4x+6=-106-10x |

Equations solver categories